Dunia Perempuan dalam Kumpulan Cerita Pendek “Jeramba-Jeramba Malam” Karya Mimi La Rose, Dkk - Tri Astuti (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
This research aims to describe the world of women in a collection of short stories Jeramba-jeramba Malam by Mimi La Rose, et al. The research method used is a qualitative description method with content analysis techniques. Data collection is done through documentation techniques. The collected data were analyzed based on the concept of interactive techniques, including data reduction, data presentation, data analysis, and drawing conclusions. The results of the study, the world of women domestically, publicly, as well as a combination of domestic and public. The picture of the world of women publicly gives birth to the image of women who are independent, strong, decisive, brave, ignorant, and ignoring women's honor; domestically, giving birth to the image of a woman who is gentle, patient, loyal, weak / helpless, resigned / accepts the provisions of destiny; while the combination of domestic and public breeds an image of women who are strong, decisive, independent, less responsible, ignorant, unfaithful. From the author's perspective, the author generally describes the world of women domestically. The tendency of women writers to describe the domestic world of women because the authors are still influenced by the traditions and mindset of the community who think women are better at home, as the person in charge of the household, while male authors tend to see the world of women physically and psychologically. Keywords: Analysis, Women's World, Short Stories of Night Servants